Storage changes in U.P. Pilot Food Plant reconstituted milk - Galvez, Divina I.; De Leon, Sonia Y. (1965)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Milk -- Storage